Value of an Additional Review for Eosinophil Quantification in Esophageal Biopsies. (July 2015) - Stucke, Emily M.; Clarridge, Katherine E.; Collins, Margaret H.; Henderson, Carol J.; Martin, Lisa J.; Rothenberg, Marc E.
Abstract : ABSTRACT: Eosinophilic esophagitis (EoE) requires a peak count of 15 eosinophils per high-power field (hpf). Herein, the peak eosinophil count specified by a pathologist was compared with the second review of a research assistant. Of 477 biopsies, 106 had a peak count between 1 and 14 eosinophils/hpf cited in the pathology report, and 23/106 (22%) had ≥15 eosinophils/hpf on second review. The pathology report detected potential EoE with 99% specificity, but 80% sensitivity. As such, an additional review of esophageal biopsies yields higher eosinophil counts in ∼5% of cases. We propose that biopsies with a count between 1 and 14 eosinophils/hpf require further investigation because ∼22% may yield a potential EoE diagnosis. Abstract : Supplemental Digital Content is available in the text